STRUCTURAL FEATURES OF LITERARY AND CRITICAL ARTICLES OF THE SILVER AGE - M.A. Jurayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the features of the content of literary and critical articles of the Silver Age. The coverage of the topic is based on the conclusions of many scientists.